Enhanced Bioavailability of AC1497, a Novel Anticancer Drug Candidate, via a Self-Nanoemulsifying Drug Delivery System - Kshitis Chandra Baral; Jae-Geun Song; Sang Hoon Lee; Rajiv Bajracharya; Godesi Sreenivasulu; Minkyoung Kim; Kyeong Lee; Hyo-Kyung Han (MDPI AG, 2021)
AC1497 is an effective dual inhibitor of malate dehydrogenase 1 and 2 targeting cancer metabolism. However, its poor aqueous solubility results in low bioavailability, limiting its clinical development. This study was conducted to develop an effective self-nanoemulsifying drug delivery system (SNEDDS) of AC1497 to improve its oral absorption. Based on the solubility of AC1497 in various oils, surfactants, and cosurfactants, Capryol 90, Kolliphor RH40, and Transcutol HP were selected as the components of SNEDDS. After testing various weight ratios of Capryol 90 (20-30%), Kolliphor RH40 (35-70%), and Transcutol HP (10-35%), SNEDDS-F4 containing 20% Capryol 90, 45% Kolliphor RH40, and 35% Transcutol HP was identified as an optimal SNEDDS with a narrow size distribution (17.8 ± 0.36 nm) and high encapsulation efficiency (93.6 ± 2.28%). Drug release from SNEDDS-F4 was rapid, with approximately 80% of AC1497 release in 10 min while the dissolution of the drug powder was minimal (<2%). Furthermore, SNEDDS-F4 significantly improved the oral absorption of AC1497 in rats. The maximum plasma concentration and area under the plasma concentration-time curve of AC1497 were, respectively 6.82- and 3.14-fold higher for SNEDDS-F4 than for the drug powder. In conclusion, SNEDDS-F4 with Capryol 90, Kolliphor RH40, and Transcutol HP (20:45:35, w/w) effectively improves the solubility and oral absorption of AC1497.